HUBUNGAN ANTARA GAYA BELAJAR DAN AKTIVITAS BELAJAR TERHADAP PEMAHAMAN KONSEP MATA PELAJARAN BIOLOGI SISWA KELAS XI SMA - Asrijal Asrijal; Syahruni Karim; Muhammad Al Muhajir; Amirah Mustarin (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This research is a quantitative descriptive study that aims to obtain an overview of the relationship between learning styles and learning activities toward students' conceptual understanding of biology subjects at SMA Addaraen Makassar. This study involves three variables: the independent variables are learning style and learning activity, while the dependent variable is the understanding of biology concepts. The population in this study consisted of all 18 students in Grade XI at SMA Addaraen Makassar. The data analysis techniques used were descriptive statistics and inferential statistics for hypothesis testing. The results of the analysis showed that the students' learning styles obtained an average score of 67.75, categorized as